Macroporous scaffolds: Molecular brushes based on oligo(lactic acid)–amino acid–indomethacin conjugated poly(norbornene)s. (January 2018) - Sutthasupa, Sutthira; Sanda, Fumio
Graphical abstract: Highlights: Macroporous scaffolds were developed from molecular brushes. The brushes based on oligo(lactic acid)–amino acid–indomethacin conjugated poly(norbornene)s. The scaffolds released indomethacin conjugated in an acidic environment. The scaffolds did not exhibit toxicity to HEK 293 cells. Abstract: Leucine-derived norbornene monomer (1 ), oligo(lactic acid)-derived norborne macromonomer (2 ) and indomethacin-conjugated norbornene (3 ) were synthesized and polymerized using the Grubbs ruthenium complex as a catalyst. Macromonomer2 was synthesized by the ring-opening polymerization of lactide using 5-norbornene-2, 3- exo, exo -dimethanol as an initiator and 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU) as a catalyst. The corresponding polymers, poly(1 ), poly(2 ), poly(3 ) and copolymers with number-average molecular weights ( Mn ) ranging from 14 000 to 360 000 were obtained in 73–95% yields. Poly(2 ) formed scaffolds by simply drying under reduced pressure presumably due to the brush-like structure causing entanglement of the polymer chains. The compressive strength of poly(2 ) scaffold increased as increasing the polylactide chain length. The compressive strength of the scaffolds obtained from the copolymers ranged from 0.222 to 0.587 MPa in accordance with the monomer unit ratios. SEM revealed the presence of pores around 5–10 µm diameters, together with larger pores dispersed in the range of 50–300 µm diameters. TEM demonstrated the presence of polymer networks. The conjugated indomethacin was gradually released by incubation under acidic condition (pH 5.7) at 37 °C. The results of % cell viability, release of LDH activity and cell morphology assays revealed that the obtained scaffolds did not exhibit cytotoxicity toward HEK 293 cells.